Index selection of tropical maize genotypes for nitrogen use efficiency - Granato,Ítalo Stefanine Correia (2014)
Nitrogen (N) limitation in maize crops is related to the fact that the efficiency of nitrogen fertilization in maize does not exceed 50%, primarily due to volatilization, denitrification and soil leaching. Therefore, the development of new nitrogen use efficient (NUE) cultivars is necessary. The aim of the present study was to develop indices for the accurate selection of NUE maize genotypes for use in conditions of both high and low N availability. The experiment was conducted in a greenhouse (20º45'14"S; 42º52'53"W) at the Federal University of Viçosa during October 2010. A total of 39 experimental hybrid combinations and 14 maize lines differing in NUE were evaluated under two N availability conditions. We determined the relative importance of the studied characters using principal component analysis, factor analysis and by developing efficient selection indices. We conclude that indirect and early selection of tropical maize genotypes can be performed using the indices I HN = 0.022 SDM + 0.35 RSDM + 0.35 RL A + 0.35 NUE for high N availability environments and I LN = -0.06 RSDM + 0.35 RSA A + 0.35 RL A + 0.39 SDM for low N availability environments.